Foraminiferal Evidence of Younger Dryas Age Cooling on the British Columbia Shelf - Patterson, R.; Guilbault, Jean-Pierre; Thomson, Richard; Luternauer, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTCluster analysis of foraminifera from a ~12,000-9000 radiocarbon year old piston core from Goose Island Trough, Queen Charlotte Sound, indicates that a cold interval correlative with the Younger Dryas stadial occurred during a shallow water phase. The reduction in depth was caused by the passage across the area, between 11,500 and 10,000 years BP, of a glacial forebulge associated with the retreat of the Late Wisconsinian ice sheets. Published sedimentological evidence indicate that water depths decreased to ~75-90 m, placing the site above the permanent North Pacific pycnocline (100 m). Low salinity-near glacial conditions, at these depths, between -11,100 and 10,000 years BP were recognized by abundant populations of Cassidulina reniforme and lslandiella helenae. This cold interval has also been recognized in cores from elsewhere in Queen Charlotte Sound. The depressed salinity and temperature may have resulted from a modification of regional weather patterns. Decreased mean continental summer temperatures could have reduced the seasonal influence of the North Pacific High and lengthened that of the Aleutian Low. This would have resulted in a near continuous onshore surface Ekman transport and enhanced coastal runoff, effectively blocking the movement onto the shelf of deep, saline, warm water of the California Undercurrent. The resultant isolated inshore basin comprised of present-day Hecate Strait and Queen Charlotte Sound is tentatively named the "Hecate Sea". By ~10,000 years BP, weather and ocean circulation had returned to near modern patterns as indicated by the disappearance of lslandiella helenae and by the development of an Epistominella vitrea - dominated biofacies.